"Just ask me what it means to live with dementia" – people with mild dementia's strategies and techniques shared through in‐depth qualitative interviews. Issue 13 (4th January 2021) - Thoft, Diana Schack; Ward, Alison
Abstract: This article presents results from interviews with twelve persons with mild dementia about how life had changed since they received their diagnosis, exploring their experiences of dementia and how they manage life by using different strategies and techniques. Knowledge about how people with mild dementia experience life is important to explore through their unique perspective, providing clinical practice with knowledge to improve dementia care. Twelve participants were recruited at a Danish school service for people with mild dementia where they receive cognitive stimulation. Semi‐structured interviews were conducted, video recorded, transcribed and analysed by using Max Van Manen's five lifeworld existentials: spatiality, corporeality, temporality, relationality and materiality. SRQR checklist was used. Five themes were identified, illustrating the dilemmas and challenges the participants experience, as all existentials are compromised in some way: living a social and active life regardless of difficulties; trying to look at the bright side of life with dementia; it takes time to adapt but at the same time, time is being lost; it is possible to learn, but it is challenging; to try to remember but keep forgetting. The article concludes that all existentials are negatively influenced by dementia, setting the lifeworld of the participants under pressure. However, they still try to live their lives regardless of the difficulties. The study shows it is possible for people with mild dementia to describe their lived experience of dementia and what strategies and techniques they use to manage life. The experienced dilemmas and challenges in the lifeworld of people with mild dementia are of great relevance to be aware of and address in clinical practice. To support people with dementia to identify relevant strategies and techniques, as expressed in the study, that can support them managing life with dementia.